2019
DOI: 10.1002/ajcp.12336
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Social Support in Promoting Community Integration: An Integrated Literature Review

Abstract: Highlights Comprehensively reviews the impact of social support on community integration Responds to the call to reengage in community mental health research from special issue of AJCP Emphasizes the importance of social support and community integration for individuals with serious mental illnesses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Among migrant populations, integration strategies could improve their mental health while increasing the acceptability of diversity, reducing discrimination towards immigrants, thereby contributing to better mental health [35,46]. Communitylevel interventions providing immigrants opportunities to increase social networking among members of the same country and those native-born in a host country may be helpful resources for improving mental health among immigrants [21,47]. It is plausible that one who has a better understanding of the host culture might have inspired opportunities to participate in social activities with host country members, leading to an improved sense of belonging, which are significant predictors of better mental health.…”
Section: Implications Of Our Findings To Policy and Practicementioning
confidence: 99%
“…Among migrant populations, integration strategies could improve their mental health while increasing the acceptability of diversity, reducing discrimination towards immigrants, thereby contributing to better mental health [35,46]. Communitylevel interventions providing immigrants opportunities to increase social networking among members of the same country and those native-born in a host country may be helpful resources for improving mental health among immigrants [21,47]. It is plausible that one who has a better understanding of the host culture might have inspired opportunities to participate in social activities with host country members, leading to an improved sense of belonging, which are significant predictors of better mental health.…”
Section: Implications Of Our Findings To Policy and Practicementioning
confidence: 99%
“…play an important role in promoting community integration for people with mental illness (Terry & Townley, 2019). Social isolation has been identified as an obstacle to community integration (Nemiroff et al, 2011) while social support was connected to higher physical and psychological integration .…”
Section: What This Paper Adds?mentioning
confidence: 99%
“…Individuals in recovery from substance use disorders may also benefit from social network focused therapies, connections with peer support, or interventions aimed to build social and recovery capital as well as a sense of self-worth (Boisvert et al, 2008; Collins et al, 2012; Henwood et al, 2017; Neale & Stevenson, 2015; Stein et al, 2008). Future investigations might also consider interventions that engender social support within consumer-run or self-help organizations (Nelson et al, 2007), or within supported employment (Terry & Townley, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, abstinence may be promoted for individuals who have network members who support abstinence (Kelly et al, 2012). Finally, a comprehensive review of social support for individuals with serious mental illnesses found that social support from a variety of sources contributes to community integration, mental health, quality of life, and overall well-being (Terry & Townley, 2019).…”
mentioning
confidence: 99%